The effects of ultra-loose monetary policies on inequality - Grégory Claeys; Zsolt M. Darvas; Álvaro Leandro; Thomas Walsh (Bruegel, 2015)
Low interest rates, asset purchases and other accommodative monetary policy measures tend to increase asset prices and thereby benefit the wealthier segments of society, at least in the short-term, given that asset holdings are mainly concentrated among richest households. Such policies also support employment, economic activity, incomes and inflation, which can benefit the poor and middle-class, which have incomes more dependent on employment and which tend to spend a large share of their income on debt service.Monetary policy should focus on its mandate, while fiscal and social policies should address widening inequalities by revising the national social redistribution systems for improved efficiency, intergenerational equity and fair burden sharing between the wealthy and poor.
Keywords: 330